Cyber security in Developing World towards Excellency by 2026 – Opportunities, Policies - Satheesh Kumar, N; Mihret, Zelalem (International Journal of Computer Sciences and Engineering, 2025)
Information and communication technology (ICT) is playing a major role in the development of socio economic related issues. Some countries in the globe have taken advantage with the effectiveness of ICT, Cyberspace and are in the process of transforming their economies into knowledge and information based economies. These benefits are being challenged by the increasing cyber threats where there is no global conscious on how to regulate cyberspace even through several countries having their own cyber security policies but without proper measures. The current setup of the internet enables developing countries to work together as a global village. The goal of this paper are to help policy makers, businesses, and societal organizations to better prepare for the technological changes ahead and enable all stakeholders to consider how present day policy choices might influence future outcome. In our paper we propose cyber security 2026 model along with methodology which concentrate on the several components to form a framework for trust and online security.